Politicisation, democratisation and EU identity national EU discourses in Germany and France - Wiesner, Claudia (Routledge, Taylor & Francis Group, 2024)
Zusammenfassung: "This book discusses and conceptualises key questions for the study of politicisation and democratisation of the EU, as well as EU identity. Comparatively analysing two prototypical cases, namely the discourses related to the ratification of the EU Constitutional Treaty in 2005 in Germany and France, and their outcomes it addresses key questions: Why is it necessary to democratise the EU? Can increasing EU politicisation help democratising the EU or will it put EU integration in danger? What is it that unites the European Union as a polity? Discussing then the two cases in relation to more current events such as Brexit and the French elections of 2022, the book develops key theoretical models and delivers profound findings on EU democratisation, identity, politicisation and contestation: This book will be of key interest to scholars and students of European Union studies/politics, democratic theory, discourse analysis and more broadly to comparative politics"--(Provided by publisher.)
Keywords: Europäische Union; Democratization--European Union countries.; National characteristics, European.; Group identity--Political aspects--European Union countries.; Political participation--European Union countries.; Political culture--European Union countries.; Political culture--Germany.; Political culture--France.; European Union countries--Politics and government--21st century.; Démocratisation--Pays de l'Union européenne.; Européens.; Identité collective--Aspect politique--Pays de l'Union européenne.; Participation politique--Pays de l'Union européenne.; Politische Kultur; Europagedanke; Frankreich; Deutschland